Pembinaan Mental Rohani Islam: Studi Fenomenologis pada Prajurit Tentara Nasional Indonesia di Provinsi Lampung - Frimayanti, Ade Imelda; Rusdiani, Atik; Yuni Saputri, Rima (UIR Press, 2025)
This study examines the Islamic spiritual development strategies implemented for soldiers of the Indonesian National Armed Forces (TNI) in Lampung Province and their implications for spiritual well-being. A qualitative phenomenological approach was employed to explore soldiers’ subjective experiences, with data collected through participant observation, semi-structured interviews with five informants (n = 5), and document analysis. Data were analyzed thematically to identify the forms of practice, implementation challenges, and perceived outcomes of the program. The findings indicate that spiritual development was conducted through congregational prayer, Qur’anic recitation, dhikr, religious study sessions, spiritual counseling, spiritual retreats, and social service activities, which collectively contributed to enhanced discipline, emotional stability, and strengthened religious commitment among soldiers. However, program effectiveness was constrained by demanding military schedules and variability in counselors’ competencies. The study recommends capacity-building for spiritual counselors, scheduling adjustments, and systematic program evaluation to improve intervention quality. The research is limited by its small sample size and single-site focus, which restrict the generalizability of the findings. Future research is recommended to employ mixed-method designs with larger samples to assess quantitative impacts on discipline, mental well-being, and religiosity